2007
DOI: 10.1029/2006ja011958
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray detector response to transient solar modulation: Forbush decreases

Abstract: [1] The observed modulation of galactic cosmic ray (GCR) intensity, on time and spatial scales, contains information regarding their transport in the heliosphere. One way to extract crucial information from the data is to study the rigidity dependence of modulation. A methodology is described to study the rigidity dependence of the short-term variations in galactic cosmic ray intensity Earth, in terms of the median rigidity of detector response (R m ) to cosmic ray spectrum. We define R m as the rigidity below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
(67 reference statements)
3
28
0
Order By: Relevance
“…So, over solar cycle 21 the mean energy of CL/NM changes by about 1.5 GeV ($ 16%). We obtained similar results for solar cycle variations of the median rigidity of response for CL/NM using coupling functions derived by Nagashima et al (1989); the reader may refer to Ahluwalia and Fikani (2007). The modulation function also undergoes very similar variations.…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…So, over solar cycle 21 the mean energy of CL/NM changes by about 1.5 GeV ($ 16%). We obtained similar results for solar cycle variations of the median rigidity of response for CL/NM using coupling functions derived by Nagashima et al (1989); the reader may refer to Ahluwalia and Fikani (2007). The modulation function also undergoes very similar variations.…”
Section: Methodssupporting
confidence: 71%
“…We also suspected that the median rigidity (energy) of response for the penetrating proton channel on IMP 8 is an underestimate (Ahluwalia et al, 2006). These impressions were reinforced in our recent study of the transient solar modulations (Forbush decreases) for three solar cycles (Ahluwalia and Fikani, 2007). In both studies we showed that the radial diffusion coefficient (k) varies inversely with the median rigidity of detector response (Rm) for positive (A > 0) as well as negative (A < 0) solar cycles.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, for different NMs we can compare the computed M(E eff ) with observational data of the NM count rates. Note that the effective energy is quite different from the median rigidity below which lies 50% of detector counting rate [Ahluwalia and Fikani, 2007], widely used for transient cosmic ray solar modulation studies [Ahluwalia et al, 2014]. Table 2 shows the local geomagnetic cutoff rigidity P c and the corresponding effective energy E eff of NMs used in our work.…”
Section: Gcr Datamentioning
confidence: 99%
“…This requirement is acceptably satisfied by Kiel and Rome neutron monitors which we use in our analysis; for Kiel neutron monitor R m = 2.29 GV and for Rome neutron monitor R m = 6.32 GV. Ahluwalia and Fikani (2007) demonstrated that the median rigidity of the response of a detector can be used as an alternative to the cut-off rigidity. The median rigidity for the Kiel neutron monitor is 17 GV and for Rome it is 23 GV.…”
Section: Experimental Datamentioning
confidence: 99%